2021
DOI: 10.1021/acs.jpcc.1c05786
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Tetrel-Based Neutral Frustrated Lewis Pairs for Catalytic Hydrogenation

Abstract: Frustrated Lewis pair (FLP) chemistry has gained significant attention in the past decade as the main group hydrogenation catalysts. The majority of the reported FLP catalysts utilize either boron-containing Lewis acids (LAs) or alternatively isolobal and iso­(valence)­electronic tetrylium analogues for hydrogenation. Recently, a new family of intramolecular FLPs R3E-CH2-PR′2 (E = Si, Ge, Sn) featuring neutral sp3 tetrel atoms as LA centers were reported for activation of a range of small molecules under ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Natural Bonding Orbital (NBO) Study. For a better understanding about the electron transfer (ET) process, 29,30,36 Natural bonding orbital (NBO) analysis is also conducted. The analysis revealed two significant interactions among P( t Bu) 3 , [(CH 3 ) 2 CH] 2 S 2 , and B(C 2 NBSHF 2 ) 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural Bonding Orbital (NBO) Study. For a better understanding about the electron transfer (ET) process, 29,30,36 Natural bonding orbital (NBO) analysis is also conducted. The analysis revealed two significant interactions among P( t Bu) 3 , [(CH 3 ) 2 CH] 2 S 2 , and B(C 2 NBSHF 2 ) 3 .…”
Section: Resultsmentioning
confidence: 99%
“…FLPs employ sterically demanding groups to prevent the formation of stable Lewis acid–base adducts, thereby maintaining synergistic Lewis acidic and basic effects. This concept has been applied to achieve metal-free hydrogenation and activation of various small molecules, such as H 2 , THF, CO 2 , N 2 O, alkenes, and terminal alkynes. The experimental studies of FLPs have received significant theoretical attention. , The ability of FLPs to cleave S–S bonds was demonstrated by Stephan and co-workers in 2009. They found that the S–S bond of R–S–S–R (R = Ph or i Pr) could be readily cleaved by FLPs, such as ( t Bu) 3 P/B­(C 6 F 5 ) 3 , under ambient conditions (25 °C, 1 atm), yielding thiophosphonium thioborate zwitterions.…”
Section: Introductionmentioning
confidence: 99%
“…136 Similarly, Pati and co-workers computationally explored the ability of the FLP system (F 5 C 2 ) 3 E–CH 2 –D( t Bu) 2 where E = Si, Ge, Sn and D = P, N to act as hydrogenation catalysts using CO 2 as a substrate. 137 For the FLPs where D = N, simultaneous proton and hydride migration take place, whereas for D = P FLPs, proton transfer is followed by hydride transfer. NBO analysis shows that LP(O) → σ* (D–H) and σ(E–H) → π* (CO) dominate along the energy profile.…”
Section: Group 14 Lewis Acidsmentioning
confidence: 99%
“…Results also suggest switching the donor site from P to N significantly affects the H 2 activation profiles as the latter FLPs follow a synchronous mechanism for H 2 activation, resulting in lower activation barriers. Inspired by this, the ability of these geminal FLPs to perform as hydrogenation catalysts, particularly towards C=X (X=O, N) are also computationally investigated [58] …”
Section: Tin‐based Lewis Acidsmentioning
confidence: 99%
“…Inspired by this, the ability of these geminal FLPs to perform as hydrogenation catalysts, particularly towards C=X (X=O, N) are also computationally investigated. [58]…”
Section: Tin-based Lewis Acidsmentioning
confidence: 99%